2010
DOI: 10.1523/jneurosci.2289-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Efferent Pathways Modulate Hyperactivity in Inferior Colliculus

Abstract: Animal models have demonstrated that mild hearing loss caused by acoustic trauma results in spontaneous hyperactivity in the central auditory pathways. This hyperactivity has been hypothesized to be involved in the generation of tinnitus, a phantom auditory sensation. We have recently shown that such hyperactivity, recorded in the inferior colliculus, is still dependent on cochlear neural output for some time after recovery (up to 6 weeks). We have now studied the capacity of an intrinsic efferent system, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
30
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 71 publications
10
30
0
1
Order By: Relevance
“…Each point represents the mean Ϯ SE of activity profiles from all animals in the sample, whose size (n) is indicated. guinea pigs have consistently shown increases in mean spontaneous activity 1-4 wk following exposure to a 10-kHz tone for 1-2 h (Dong et al 2010a(Dong et al , 2010bMulders and Robertson, 2009;Mulders et al, 2010Mulders et al, , 2011. Our results in the hamster are most similar to the changes observed in guinea pigs by Mulders and colleagues.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Each point represents the mean Ϯ SE of activity profiles from all animals in the sample, whose size (n) is indicated. guinea pigs have consistently shown increases in mean spontaneous activity 1-4 wk following exposure to a 10-kHz tone for 1-2 h (Dong et al 2010a(Dong et al , 2010bMulders and Robertson, 2009;Mulders et al, 2010Mulders et al, , 2011. Our results in the hamster are most similar to the changes observed in guinea pigs by Mulders and colleagues.…”
Section: Discussionsupporting
confidence: 84%
“…Such changes have been well characterized at the multiunit and single-unit levels in structures as diverse as the dorsal cochlear nucleus (DCN) (Brozoski et al, 2002;Finlayson and Kaltenbach 2009;Kaltenbach and McCaslin 1996;Kaltenbach et al 2000Kaltenbach et al , 2002Middleton et al 2011;Shore et al 2008), the ventral cochlear nucleus (VCN) (Vogler et al 2011), the inferior colliculus (IC) (Bauer et al 2008;Chen and Jastreboff 1995;Dong et al 2009Dong et al , 2010aDong et al , 2010bJastreboff and Sasaki 1986;Mulders and Robertson 2009;Mulders et al 2010Wallhäusser-Franke et al 2003), and the auditory cortex (Eggermont and Kenmochi 1998;Eggermont 2005, 2006;Ochi and Eggermont 1997;Seki and Eggermont 2003;Wallhäusser-Franke et al 1996), suggesting that tinnitus may be a system-wide pathology. Indeed, functional imaging studies in both animals and human subjects with tinnitus show clear evidence of hyperactivation of centers both within and beyond the auditory system (Brozoski et al 2007;Eichhammer et al 2007;Langguth et al 2006;Lanting et al 2008;Lobarinas et al 2008;Lockwood et al 1998;Melcher et al 2000Melcher et al , 2009Reyes et al 2002).…”
mentioning
confidence: 99%
“…In agreement with another study performed on rats, this range was shifted to higher frequencies outside the frequency range of sound-induced acoustic trauma (Wang et al 2009). In agreement with other studies (Salvi et al 1996;Brozoski et al 2002;Mulders and Robertson 2009;Dong et al 2010;Mulders et al 2010), we also found that behavioral signs of tinnitus were accompanied by an elevation of spontaneous activity in inferior colliculus neurons. Although, our electrophysiological results confirm that sound exposure leads to hyperactivity, it does not explain the origin of this hyperactivity.…”
Section: Figsupporting
confidence: 93%
“…If spontaneous hyperactivity is indeed involved in the generation of tinnitus (Brozoski et al, 2002;Bauer et al, 2008), then our results could indicate a beneficial effect of OC system activation on tinnitus. Mulders et al (2010) find that the suppressive effects on spontaneous activity lasted after the stimulation had ceased, is consistent with a role for the OC system in residual inhibition, a temporary reduction of tinnitus experienced in tinnitus patients that persists for a few seconds after masking sounds are turned off (Vernon and Meikle, 2003;Roberts et al, 2008). Likewise, activation of the OC system could be a contributory mechanism to the often beneficial effects of masking sounds on the perception of tinnitus (Jastreboff, …”
Section: Introductionsupporting
confidence: 57%
“…This hypothesis is supported by the fact that the hyperactivity seems restricted to tonotopic regions broadly corresponding to the area of hearing loss as shown in cochlear nucleus, the central nucleus of the inferior colliculus, and the auditory cortex (Dong et al, 2009;) and the observation in human studies that there is a strong correlation between the tinnitus pitch and the hearing loss frequencies (Norena et al, 2002;Eggermont and Roberts, 2004). The study of Mulders et al (2010) indicate a strong effect of stimulation of the medial olivocochlear (OC) system on hyperactivity caused by acoustic trauma. This demonstration that an intrinsic control system can modify maladaptive plastic phenomena in the auditory pathway, could have important clinical implications.…”
Section: Introductionmentioning
confidence: 86%